Magnitude, Frequency, and Accumulation: Workload Among Injured and Uninjured Youth Basketball Players - Benson, Lauren C.; Owoeye, Oluwatoyosi B. A.; Räisänen, Anu M.; Stilling, Carlyn; Edwards, W. Brent; Emery, Carolyn A. (Frontiers in Sports and Active Living, 2021)
Overuse injuries are common in basketball. Wearable technology enables workload to be monitored in sport settings. However, workload-injury models lack biological basis both in the metrics recorded and how workload is accumulated. We introduce a new metric for monitoring workload: weighted jump height, where each jump height is weighted to represent the expected effect of the jump magnitude on damage to tendon. The objectives of this study were to use principal components analysis (PCA) to identify distinct modes of variation in all workload metrics accumulated over 1, 2, 3 and 4 weeks, and to examine differences among the modes of variation in workload metrics between participants prior to injury and uninjured participants. Forty-nine youth basketball players participated in their typical basketball practices and games and lower extremity injuries were classified as patellar or Achilles tendinopathy, other overuse, or acute. An inertial measurement unit recorded the number and height of all jumps, and session rating of perceived exertion (sRPE) was recorded. The previous 1-, 2-, 3- and 4-week workloads of jump count, jump height, weighted jump height and sRPE were summed for each participant-week. PCA explained the variance in the accumulated workload variables. Using the retained PCs, the difference between the workload of injured participants in the week before injury and the mean workload of uninjured participants was described for patellar or Achilles tendinopathy, overuse lower extremity injury and any lower extremity injury. Participants with patellar or Achilles tendinopathy and overuse lower extremity injuries had a low workload magnitude for all variables in the 1, 2, 3, and 4 weeks prior to injury compared to the weeks prior to no injury. Participants with overuse lower extremity injuries and any lower extremity injury had a high previous 1-week workload for all variables along with a low previous 3- and 4-week jump count, jump height and weighted jump height prior to injury compared to the weeks prior to no injury. Weighted jump height represents the cumulative damage experienced by tissues due to repetitive loads. Injured youth basketball athletes had a low previous 3- and 4-week workload coupled with a high previous 1-week workload.